A novel high-affinity potassium transporter SeHKT1;2 from halophyte Salicornia europaea shows strong selectivity for Na+ rather than K+ - Haxim, Yakupjan; Wang, Lei; Pan, Zhendong; Fan, Xiaorong; Ma, Jinbiao (Frontiers in Plant Science, 2023)
High-affinity K+ transporters (HKTs) are known as transmembrane cation transporters and are involved in Na+ or Na+-K+ transport in plants. In this study, a novel HKT gene SeHKT1;2 was isolated and characterized from the halophyte, Salicornia europaea. It belongs to subfamily I of HKT and shows homology with other halophyte HKT proteins. Functional characterization of SeHKT1;2 indicated that it contributes to facilitating Na+ uptake in Na+-sensitive yeast strains G19, however, cannot rescue the K+ uptake-defective phenotype of yeast strain CY162, demonstrating SeHKT1;2 selectively transports Na+ rather than K+. The addition of K+ along with NaCl relieved the Na+ sensitivity. Furthermore, heterologous expression of SeHKT1;2 in sos1 mutant of Arabidopsis thaliana increased salt sensitivity and could not rescued the transgenic plants. This study will provide valuable gene resources for improving the salt tolerance in other crops by genetic engineering.